Emerging trends in Indian politics : the 15th general election - Mehra, Ajay K. (New Delhi : Routledge, 2010)
Contributed articles.
"Centre for Public Affaris; Heinrich Boll Stiftung, India."
Includes bibliographical references (pages 349-365) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: India. -- Parliament. -- Lok Sabha -- Elections, 2009.; India -- Politics and government -- 21st century; Electronic books